2013
DOI: 10.1111/all.12302
|View full text |Cite
|
Sign up to set email alerts
|

Laminin γ-1 and collagen α-1 (VI) chain are galactose-α-1,3-galactose-bound allergens in beef

Abstract: The carbohydrate moiety (α-Gal) on laminin γ-1 and collagen α-1 (VI) chain are possibly common IgE-reactive proteins in the Japanese patients with beef allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…Recently, it has been reported that laminin c-1 and collagen a-1 (VI) chain from beef are a-Gal-containing allergens (21). Those findings were in line with previous research demonstrating cross-reactivity of red meat with gelatin, a derivative of collagen (7), and that laminins contain a-Gal at the post-translational modification level (22).…”
supporting
confidence: 89%
“…Recently, it has been reported that laminin c-1 and collagen a-1 (VI) chain from beef are a-Gal-containing allergens (21). Those findings were in line with previous research demonstrating cross-reactivity of red meat with gelatin, a derivative of collagen (7), and that laminins contain a-Gal at the post-translational modification level (22).…”
supporting
confidence: 89%
“…Proteomics is an important tool in revealing and assessing the physicochemical properties of food allergens 16, 17 and several proteomics studies have identified α-Gal-containing meat proteins that react with IgE from red meat-allergic patients 18–20 . Some of these proteins remain stable to thermal processing, showing that the allergenic properties are preserved in cooked meat 19, 20 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Briefly, proteins were separated using SDS-polyacrylamide gel electrophoresis (SDS-PAGE). Serum shrimp-specific IgE, crab-specific IgE, squid-specific IgE, tropomyosin-specific IgE, Der p 1 (peptidase 1)-specific IgE, and Der p 10 (tropomyosin)-specific IgE levels were detected by the CAP-fluorescent-enzyme immunoassays (CAP-FEIA) (ImmunoCAP â , ThermoFischer Scientific, Uppsala, Sweden).…”
Section: Measurement Of Serum Allergen-specific Igementioning
confidence: 99%
“…20 Briefly, water-soluble and water-insoluble shrimp proteins were separated on 12.5% SDS-PAGE under reducing condition and electrophoretically transferred to a PVDF membrane. 20 Briefly, water-soluble and water-insoluble shrimp proteins were separated on 12.5% SDS-PAGE under reducing condition and electrophoretically transferred to a PVDF membrane.…”
Section: Sodium Periodate Treatmentmentioning
confidence: 99%